Strengthening the Potential of the Aviation Industry as a Bilateral Cooperation between Indonesia and Germany - Jeneva, New; Permasari, Nur Laila; Izzati, Meydina; Martha, Putri; Siswajanthy, Farahdinny (PT FORMOSA CENDEKIA GLOBAL, 2024)
International cooperation plays a vital role in fostering economic growth, technological advancement, and industrial integration. This study aims to analyze the potential of bilateral cooperation between Indonesia and Germany in the aviation industry, focusing on the N219 aircraft project. The research employs a qualitative approach through a review of data from theses, journals, and online sources, supporting an in-depth exploration of cooperation mechanisms, challenges, and opportunities. The findings indicate that this collaboration strengthens Indonesia's position in the international supply chain by advancing technological capabilities and enhancing the aviation industry. Furthermore, Germany's support in technology and supply chain integration boosts the global competitiveness of the N219 project. Key challenges include regulatory harmonization and workforce development. However, the opportunities for sustainable innovation and economic growth are highly promising, positioning this partnership as a strategic model in high-tech sectors.